Sustainable food packaging: Valorising wheat straw fibres for tuning PHBV-based composites properties - Berthet, M.-A.; Angellier-Coussy, H.; Chea, V.; Guillard, V.; Gastaldi, E.; Gontard, N. (Composites. Part A, Applied science and manufacturing, 2015)
The present work aims at investigating the impact of wheat straw fibres (WSF) size, morphology and content on the process-ability and functional properties (mechanical properties and water vapour permeability) of PHBV-based composites. For that purpose, three types of fibres obtained by successive grindings (from the micrometric up to the millimetric scale) were used. It was shown that the highest possible filler level was all the more high when decreasing fibre size (over 50wt% in the case of micrometric fibres), due to reduced film heterogeneity and improved fibre wetting by the polymer. As regards functional properties, increasing fibre size and/or content led to a significant degradation of ultimate tensile properties, while Young’s modulus was not significantly affected. At the same time, water vapour transmission rate was significantly increased from 11 up to 110gm−2day−1, which could extend the applicability of PHBV/WSF composites as food packaging materials to respiring fresh products.